Talent Management Analysis at PT Permodalan Nasional Madani Venture Capital - Widi Maryati; Nugroho B. Sukamdani; Tatan Sukwika (Transpublika Publisher, 2025)
This study analyzes the implementation of talent management at PT Permodalan Nasional Madani Venture Capital (PT PNM Venture Capital) as a venture capital company that plays a strategic role in supporting the development of micro, small, and medium enterprises (MSMEs) in Indonesia. The problems studied include unsystematic talent management planning, unintegrated recruitment, inaccurate talent placement, lack of talent with specific skills, insufficient training programs, absence of talent pool systems, and high turnover, especially in the marketing department. The research framework integrates talent management theory, Resource-Based View (RBV), Positioning Theory, Human Capital Theory, Psychological Contract Theory, Performance Management Theory, and Dynamic Capability Theory. The research employs a descriptive qualitative approach with in-depth interviews, observation, and documentation studies involving the President Director, Head of Human Resources Division, and human resources practitioners. The findings show that PT PNM Venture Capital has implemented the main components of talent management, including HR planning, recruitment, placement, development, retention, and performance assessment based on Key Performance Indicators (KPIs). However, implementation still faces obstacles including limited HR Analytics technology, lack of integrated talent pool, absence of Individual Development Plans (IDPs), and high employee turnover among those with less than one year of service. The implementation is not yet fully technology-based, data-driven, and long-term oriented. The recommendations include implementing HR Analytics and integrated digital systems, developing IDPs, strengthening succession planning and leadership development, adopting employee engagement-based retention strategy, and undertaking adaptive talent management transformation to increase competitiveness in the dynamic venture capital industry.